Program Co-Chair - Kyriacou, Efthyvoulos C. (My University, 2026)
IFMBE XIV Mediterranean Conference on Medical and Biological Engineering and Computing 2016: MEDICON 2016, March 31st-April 2nd, Paphos, Cyprus, 2016 (290 accepted papers)